2020
DOI: 10.3390/ijms21093133
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does CFTR Play in Development, Differentiation, Regeneration and Cancer?

Abstract: One of the key features associated with the substantial increase in life expectancy for individuals with CF is an elevated predisposition to cancer, firmly established by recent studies involving large cohorts. With the recent advances in cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies and the increased long-term survival rate of individuals with cystic fibrosis (CF), this is a novel challenge emerging at the forefront of this disease. However, the mechanisms linking dysfunctiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 189 publications
2
40
0
Order By: Relevance
“…Besides its function as a chloride/bicarbonate channel, CFTR has also been implicated in epithelial differentiation and regeneration [ 3 ], being, however, unclear how this occurs mechanistically. Here, we investigated whether the Krüppel-like factors (KLFs), a family of evolutionary conserved zinc finger transcription factors that regulate a variety of biological processes including proliferation, differentiation, and apoptosis [ 6 ], have an impact on CFTR expression and function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides its function as a chloride/bicarbonate channel, CFTR has also been implicated in epithelial differentiation and regeneration [ 3 ], being, however, unclear how this occurs mechanistically. Here, we investigated whether the Krüppel-like factors (KLFs), a family of evolutionary conserved zinc finger transcription factors that regulate a variety of biological processes including proliferation, differentiation, and apoptosis [ 6 ], have an impact on CFTR expression and function.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this may be due to the fact that CF cells display a partial EMT/cancer-like phenotype [ 3 ], which leads to altered signaling pathways, namely those linking KLF4 to CFTR. Indeed, KLF4 regulates gene expression through transcriptional activation or repression via either DNA binding or protein-to-protein interactions, and thus the outcome of KLF4-mediated regulation largely depends on the cellular context, e.g., the presence of oncogenic drivers among other factors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFTR has been shown to play a role in fundamental cellular processes related to differentiation, such as fetal development [4], epithelial differentiation/polarization [5], regeneration [6], and epithelial-mesenchymal transition (EMT) [7]. The multiple associations of CFTR and epithelial differentiation/EMT have been recently reviewed and reflect the idea that CF cells display a more cancer-like (vs. non-CF cells) phenotype due to the occurrence of a partial EMT [8], considered as a first stage into carcinogenesis [9]. Moreover, KLF4 has been linked to tumor metastasis through the regulation of EMT in several forms of human cancers [10].…”
Section: Introductionmentioning
confidence: 99%
“…KLF4 transcriptional profiling reveals its key role in cell-cycle regulation and epithelial differentiation [21]. Therefore, here we aim at understanding the role of KLF4 on cell proliferation, wound healing, EMT, and differentiation in the context of CF since these processes are disrupted in CF [6,8]. It has been demonstrated that KLF4 may exert very distinctive effects, depending on the cell context, i.e., its effects are dependent on the cell expression profile.…”
Section: Introductionmentioning
confidence: 99%